Morphofunctional alterations in ventral tegmental area dopamine neurons in acute and prolonged opiates withdrawal. A computational perspective. (13th May 2016) - Enrico, P.; Migliore, M.; Spiga, S.; Mulas, G.; Caboni, F.; Diana, M.
Highlights: Opiates withdrawal inhibits mesolimbic dopaminergic activity and dopamine release. These effects can be described using a biophysically plausible computational model. A specific GABA/GLU input imbalance reproduces withdrawal effects on dopamine cells. Morphological changes may influence response to morphine of dopamine cells. Down-regulation of GLU inputs may explain post-withdrawal hypodopaminergic state. Abstract: Dopamine (DA) neurons of the ventral tegmental area (VTA) play a key role in the neurobiological basis of goal-directed behaviors and addiction. Morphine (MOR) withdrawal induces acute and long-term changes in the morphology and physiology of VTA DA cells, but the mechanisms underlying these modifications are poorly understood. Because of their predictive value, computational models are a powerful tool in neurobiological research, and are often used to gain further insights and deeper understanding on the molecular and physiological mechanisms underlying the development of various psychiatric disorders. Here we present a biophysical model of a DA VTA neuron based on 3D morphological reconstruction and electrophysiological data, showing how opiates withdrawal-driven morphological and electrophysiological changes could affect the firing rate and discharge pattern. The model findings suggest how and to what extent a change in the balance of GABA/GLU inputs can take into account the experimentally observed hypofunction of VTA DA neurons during acute and prolonged withdrawal, whereas morphological changes may play a role in the increased excitability of VTA DA cell to opiate administration observed during opiate withdrawal.